2012
DOI: 10.1179/1743133611y.0000000022
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of austenitisation of ductile irons containing two different contents of manganese and copper

Abstract: This work deals with the study of austenitisation behaviour of two ductile irons: alloy A [3?18C-2?64Si-0?45Mn (wt-%)] and alloy D [3?18C-3?0Si-1?04Mn-1?13Cu (wt-%)]. Samples were austenitised at 850, 900 and 950uC with varying times and then quenched in water. Following special etching techniques, the possible nucleation sites for austenitisation (transformed to martensite on quenching) have been identified as the ferrite/cementite interfaces within the pearlite matrix as well as the pearlite colony boundarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…As for all cast irons, the Mn-Ni-resist microstructure is affected by the manganese content and cooling rate during solidification. Larger manganese content promotes the precipitation of eutectic carbide throughout austenite matrix and expected to reduce martensite start line (Ms) temperature as reported in previous report [24]. The presence of carbide in the matrix microstructure is predicted strongly detrimental to Mn-Niresist mechanical properties and processing.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…As for all cast irons, the Mn-Ni-resist microstructure is affected by the manganese content and cooling rate during solidification. Larger manganese content promotes the precipitation of eutectic carbide throughout austenite matrix and expected to reduce martensite start line (Ms) temperature as reported in previous report [24]. The presence of carbide in the matrix microstructure is predicted strongly detrimental to Mn-Niresist mechanical properties and processing.…”
Section: Introductionmentioning
confidence: 81%
“…Very high drop reading showed from 0.32 % to 0.06 % may result from the contribution of near to transition region line A1 which is in the partial melting region. This lower A1 effect by the presences of manganese as austenite stabilizer also lowered the temperatures A1 [24] and believed to drop near to 1000°C. This discovery supported the previous investigation by Ahmadabadi and Feghahati [34] which reported that a heat treatment involving an austenitising at temperature partial melting was sufficient and higher rate to reduce free carbides present in samples.…”
Section: Grain Boundary Ltf Regionmentioning
confidence: 99%